Saturn's children - Stross, Charles (London : Orbit Books, 2009)
Femmebot Freya Nakamichi, left with no one to pay for pleasure after humans become extinct in the twenty-third century, unwitting makes herself the target of some very determined humanoids when she agrees to transport a mysterious package from Mercury to Mars.
Adult.
Adult
Keywords: Androids -- Fiction; Robots -- Fiction; Science fiction; Science fiction